An MCDM model for facilities location for the float glass industry of the Philippines - Pascual, Kathleen M. (1997)
Facilities location is a vital aspect of distribution management. It plays a vital role in the distribution management of manufacturing firms as well as the service sector. In this paper, it is applied to the float glass industry in the Philippines. Similar to any decision making endeavor, cost always play a major role. In this study an integrated distribution cost model was developed. The Total Distribution Cost (TDC) takes into account the interdependence between facilities location, transportation, inventory levels. In reality however, decision makers do not solely decide based on the cost effectiveness. Often, multiple and conflicting objectives need to be simultaneously considered. Thus a goal programming model is developed and solved using sequential linear programming through the STORM software. The developed models were applied to the search process of RAGC for an external warehouse. Initially, the distribution costs were computed for all the defined external warehousing strategies. The values are assigned as the cost coefficients of the first objective that is to minimize cost of operations. The other objectives such as: minimization of capital expenditures, maximization of accessibility coefficients and strength of structure as well as the proximity coefficients are all algebraically translated into mathematical equations. Furthermore, these objectives were simultaneously considered using a goal programming model. The model is solved using the sequential linear programming capability of STORM. Various scenarios are depicted to determine the sensitivity of the model developed, and for each of these, an optimum facilities site location is identified.
Thesis (M.S. Industrial Engineering)
Keywords: Industrial location -- Mathematical models. -- Philippines; Glass trade -- Location -- Philippines